2020
DOI: 10.3390/geosciences10020042
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis in Prediction of Settlements for Spatial Prefabricated Vertical Drains Improved Soft Soil Sites

Abstract: This paper presents the quantification of uncertainties in the prediction of settlements of embankments built on prefabricated vertical drains (PVDs) improved soft soil deposits based on data collected from two well-documented projects, located in Karakore, Ethiopia, and Ballina, Australia. For this purpose, settlement prediction biases and settlement distributions were statistically computed based on analyses conducted on two Class A and Class C numerical predictions made using PLAXIS 2D finite element modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The above methods are widely and successfully used in settlement predictions and forecasts for various types of soils in different engineering projects, such as in soft soils improved with vacuum-prefabricated vertical drain [37], foundation pit of artificial fill and silty clay layers [16], subgrade filled with construction and demolition waste [10], metro shield tunnel in saturated sand [38], and the full load-settlement curve of a strip footing [39]. Although the prediction or forecast accuracy has been significantly improved, there are still errors between the predicted and observed magnitudes of settlements [40], which may be due to the application limitation and different suitability of each prediction or forecast method for varied situations and time periods. Consequently, it is particularly important to select the appropriate and reliable method according to the different soil properties and project characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The above methods are widely and successfully used in settlement predictions and forecasts for various types of soils in different engineering projects, such as in soft soils improved with vacuum-prefabricated vertical drain [37], foundation pit of artificial fill and silty clay layers [16], subgrade filled with construction and demolition waste [10], metro shield tunnel in saturated sand [38], and the full load-settlement curve of a strip footing [39]. Although the prediction or forecast accuracy has been significantly improved, there are still errors between the predicted and observed magnitudes of settlements [40], which may be due to the application limitation and different suitability of each prediction or forecast method for varied situations and time periods. Consequently, it is particularly important to select the appropriate and reliable method according to the different soil properties and project characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst Fatigue damage calculations involve several parameters, and also several combinations of environmental conditions to account for realistic operation scenarios, it is also paramount to account for the uncertainty in the models and parameters to ensure a service life of at least 20 years [4,6]. Albeit accounting for the variability of certain parameters, such as wind speed and wave height, is a common practice in the industry, other parameters are normally considered as constants, even though data has suggested that they may vary significantly [7,8]. Therefore, it is necessary to analyze the importance of those variables in terms of the structural response and reliability of the OWT.…”
Section: Introductionmentioning
confidence: 99%